Review on performance of self compacting concrete containing solid waste and bibliometric properties: A review - Hanis Nadiah, Ruslan; Khairunisa, Muthusamy; Fadzil, Mat Yahaya; Muhammad Ashraf, Fauzi; Ismail, Mohamed A.; Zuraina, Ali (Elsevier Ltd, 2024)
Self-compacting concrete (SCC) is currently an intriguing product due to its ability to reduce labour work and time. Simultaneously, the growing global population and economy result in increased solid waste accumulation in landfills. In addition to occupying a substantial portion of landfill space, the disposal of solid waste also presents widely recognized health and environmental risks to nearby areas. To address these issues, utilizing solid waste as a substitute for cement has been explored as a potential solution. Various types of solid waste, including glass, ceramic, clay brick, banana leaf ash, palm oil fuel ash (POFA), eggshell, and rice husk ash (RHA) have been studied by researchers as cement replacements in SCC. This review aims to explain the impact of using solid waste as cement replacement in SCC on both its fresh and mechanical properties. The findings of this paper review suggest that replacing 10% of POFA, 20% of RHA, 10–15% of glass, 15% of eggshell, 10% of ceramic, and 5% of clay brick for cement results in improved fresh properties and strength of SCC. The optimum percentage of substitution and its impact on the mechanical properties of SCC is determined by the unique characteristics of the waste material being used. In summary, it is deemed acceptable to utilize solid waste as a substitute for cement in SCC to enhance the fresh properties and address environmental concerns.